Functional Outcome of Volar Barton Fractures of the Distal Radius Managed with Volar Plating - Saeed, Muhammad; Khan, Muhammad Zahid; Hussain, Majid; Haq, Shafi Ul (Biological and Clinical Sciences Research Journal, 2025)
Volar Barton fractures are unstable intra-articular injuries of the distal radius that commonly result from high-energy trauma. Anatomical reduction and stable fixation are essential to restore wrist function and prevent post-traumatic arthritis. Volar locking plates are widely used, yet local outcome data remain limited. Objective: To evaluate the functional outcomes of Volar Barton fractures of the distal radius managed with volar plating. Methods: This study involved 65 patients with a confirmed diagnosis of a volar Barton’s fracture (AO/ASIF type B3). All patients underwent surgical fixation with a volar locking plate via the modified Henry approach. Guided physiotherapy was initiated two weeks after surgery. Functional outcomes were assessed using the Gartland and Werley scoring system at 6-month follow-up. Results: 65 patients were selected for this study; the majority were male (70.8%). Road traffic accidents accounted for 72.3% of cases. Assessment of functional outcomes showed that 73.8% of patients achieved excellent outcomes, 16.9% good, and 9.2% fair. Post op complications were superficial infection (6.2%), wrist stiffness (4.6%), and carpal tunnel syndrome (3.1%). Conclusion: Volar locking plate is a highly successful and safe surgical strategy for managing volar Barton’s fractures of the distal radius, with a higher proportion of excellent-to-good functional outcomes.